Analisis Penerapan Nilai-Nilai Moderasi Beragama Pada Siswa Kelas VI SDN Cangkring Bluluk Lamongan - Hakim, Nur (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
This study aims to analyze the tolerance levels of students at SDN Cangkring Bluluk Lamongan. It is a quantitative research study that utilizes a questionnaire consisting of 30 questions. The data collection technique employed a quantitative approach, involving the distribution of questionnaires to the research subjects, specifically the sixth-grade students at SDN Cangkring in Bluluk District, Lamongan Regency, totaling 11 students. Based on the research findings, the average percentage of the total scores for all respondents across all questionnaire items is 78.36%. This indicates a high level of tolerance among the sixth-grade students at SDN Cangkring Bluluk Lamongan. However, it is worth noting that one student demonstrated a less tolerant attitude towards religious differences. Consequently, early education on tolerance values is necessary at the primary education level, considering the developmental characteristics of children at that age. An effective approach to tolerance education could involve a model that encourages direct social interaction among groups of students, fostering the development of open-mindedness towards differences in others.